Slot assignment strategy to reduce loss of capacity of contiguous‐slot path requests in flexible grid optical networks. Issue 5 (1st February 2013) - Almeida, R.C.; Santos, A.F.; Assis, K.D.R.; Waldman, H.; Martins‐Filho, J.F.
Abstract : The performance improvement imparted by routing and spectrum assignment on flexible grid optical networks is a subject of current extensive investigation. Proposed is an efficient spectrum‐assignment algorithm based on reducing the loss of capacity of future bandwidth‐variable path requests. In all scenarios analysed the proposed algorithm outperformed currently investigated slot assignment algorithms.